Serological relationships between rice Hoja Blanca Virus AND Echinochloa Hoja Blanca Virus (ESP) - Madriz, Jorge (2000)
With the objective of determining whether rice hoja blanca virus (RHBV) and Echinochloa hoja blanca virus (EHBV) are serologically related, antisera were produced against the ribonucleoproteins of both viruses and used in several comparative studies. It was demonstrated that both viruses possess characteristic that separate them at this level. When compared in high resolution SDS-PAGE gels, it was observed that the EHBV nucleoprotein had a lower molecular mass than that of RHBV. The antiserum against RHBV recognizes the EHBV nucleoprotein in Western blot, indicating the presence of common epitope. Reciprocal double immunodiffusion (OUCHTERLONY) tests showed the presence of both common and unique epitopes of the nucleoproteins of both viruses.